Outcome of Myringoplasty with Temporal Fascia and With Sliced Tragal Cartilage Graft-A Comparative Study (Medicine Today, 2024)
Introduction: Myringoplasty is the surgical procedure to repair tympanic membrane perforations and thereby improving hearing, providing a dry ear, and reducing susceptibility to infections. Although there are many kinds of techniques and graft materials used, no methods have proven indisputably superior to the other. Therefore, to find out the outcome of myringoplasty using temporal fascia and sliced tragal cartilage in chronic inactive mucosal otitis media was set as an objective of the study. Materials and Methods: This cross-sectional observational study was conducted at the department of Otolaryngology & Head-Neck surgery, Shaheed Suhrawardy Medical College Hospital (ShSMCH) for six months from July 2018 to December 2018, after acceptance of the protocol and approval from IRB. Patients attending in the ShSMCH with complaints of chronic inactive mucosal otitis media were approached for inclusion of the study and final selection were done in according to the selection criteria. Ethical issues were ensured properly throughout the study period and inclusion was confirmed following signing written informed consent. All patients were randomly allocated into two groups where one group were received myringoplasty with temporalis fascia graft and another group received sliced tragal cartilage. Total 50 patients (25 patients in each group) were included, and they were subjected to details history taking, physical examination and necessary investigations. The researcher conducted all the interview and collected data were recorded into a case record form for each patient. Data analysis was done by SPSS 17. Results: Of total, 50 study population, mean age of the 32.30±10.93 SD (years) with 58% male and 42% females respectively. No significant age and gender difference is noted across the group (p>0.05). Patients having temporal fascia graft had significantly higher proportion of graft uptake in comparison to patients having sliced tragal graft (p